Network Effects and Welfare Cultures* - Bertrand, Marianne; Luttmer, Erzo F. P.; Mullainathan, Sendhil (Quarterly Journal of Economics, 2000)
We empirically examine the role of social networks in welfare participation using data on language spoken at home to better infer networks within an area. Our empirical strategy asks whether being surrounded by others who speak the same language increases welfare use more for those from high welfare-using language groups. This methodology allows us to include local area and language group fixed effects and to control for the direct effect of being surrounded by one's language group; these controls eliminate many ofthe problems in previous studies. The results strongly confirm the importance of networks in welfare participation.